2013
DOI: 10.1007/s00213-013-3004-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-retrieval extinction as reconsolidation interference: methodological issues or boundary conditions?

Abstract: Memories that are emotionally arousing generally promote the survival of species; however, the systems that modulate emotional learning can go awry, resulting in pathological conditions such as post-traumatic stress disorders, phobias, and addiction. Understanding the conditions under which emotional memories can be targeted is a major research focus as the potential to translate these methods into clinical populations carries important implications. It has been demonstrated that both fear and drug-related mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 92 publications
(167 reference statements)
8
159
0
10
Order By: Relevance
“…Seeking to capitalise on this, a number of studies have examined whether performing extinction trials within the putative 'reconsolidation window' might be more e ective at eliminating fear responses than standard extinction protocols (for review see Auber, Tedesco, Jones, Monfils, & Chiamulera, 2013;Kredlow, Unger, & Otto, 2015). The logic here is that reactivation of a memory trace opens a time-dependent window during which that trace can be modified.…”
Section: Extinctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seeking to capitalise on this, a number of studies have examined whether performing extinction trials within the putative 'reconsolidation window' might be more e ective at eliminating fear responses than standard extinction protocols (for review see Auber, Tedesco, Jones, Monfils, & Chiamulera, 2013;Kredlow, Unger, & Otto, 2015). The logic here is that reactivation of a memory trace opens a time-dependent window during which that trace can be modified.…”
Section: Extinctionmentioning
confidence: 99%
“…Attempts to replicate the original demonstration of reconsolidation-extinction in rats (Monfils et al, 2009) replications, it can be di cult to ascertain whether a putative reconsolidation process is being modulated by subtle theoretically-irrelevant procedural di erences, or theoretically-relevant 'boundary conditions' (Auber et al, 2013;Haaker et al, 2014 Since its (re)birth a decade and a half ago (Nader et al, 2000a;Przybyslawski & Sara, 1997;Sara, 2000a), the theory of reconsolidation has been buoyed by considerable empirical attention and theoretical excitement (Alberini, 2011;Besnard et al, 2012;Dudai, 2004;Nadel & Land, 2000;Nader et al, 2000b;Nader & Hardt, 2009;Nader, 2015; 21 Note that Agren et al and Bjorkstrand et al also reported correlations between blood oxygen level dependent (BOLD) activity in the amygdala and the behavioural return of fear measure. However, we have focused on whether there is a behavioural e ect consistent with reconsolidation theory.…”
Section: Cs = Plus/minusmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this type of extinction therapy had limited success in preventing relapse in humans or animals (Conklin and Tiffany, 2002;Crombag and Shaham, 2002), signifying a need for alternative cognitive-behavioral strategies for the treatment of addiction. The recent development of postretrieval extinction therapy, however, may offer a more efficacious method of reducing addiction-related memories (Auber et al, 2013;Hutton-Bedbrook and McNally, 2013). In this paradigm, the strengths of both extinction and reconsolidation are combined by presenting an extinction session during the reconsolidation process, when the memory is labile, to disrupt the consolidated memory trace.…”
Section: Post-retrieval Extinction As a Potential Treatment For Addicmentioning
confidence: 99%
“…The present study is an important step in further characterizing the boundaries within which reconsolidation update mechanisms are viable in humans. As research on reconsolidation progresses, it is becoming increasingly clear that several factors are linked to the effectiveness of targeting reconsolidation to prevent fear (Auber et al 2013). Understanding the boundary conditions (e.g., strength and age of memory) is critical in order to translate these findings to useful clinical interventions.…”
mentioning
confidence: 99%